The correlational study of the vertical jump test and wingate cycle test as a method to assess anaerobic power in road cyclists - Ulusoy, Y.; Kocak, F. (International Journal of Disabilities Sports and Health Sciences, 2023)
Road Cycling is an important sport that uses anaerobic and aerobic metabolism and especially sprinter cyclists have higher anaerobic capacity. The assessment of anaerobic power in cyclists often involves the use of the vertical jump and Wingate cycle tests. The lack of research in the field of cycling-specific tests to assess anaerobic performance has led to the improvement of existing research. The objective of this research was to investigate the correlation between the vertical jump test and the Wingate anaerobic cycling tests, both of which are often used to assess anaerobic power in road cyclists. A correlation study was conducted on 15 athletes of the Turkish national road cycling team in the 14-16 age group (15.107 ± 0.717 (SD)). The sample of the study was determined by using the convenient sampling method. On the first day, anthropometric measurements and the vertical jump test were conducted. The Wingate cycle ergometer test, lasting for a duration of 30 seconds, was administered to the participants on the second day. The computer application was used to determine the 30-second peak and average anaerobic power during the test. The results acquired from the study revealed a statistically significant positive relationship between the vertical jump performance and the peak power production measured during the Wingate cycle test (r=0.321, p<0.05). The findings indicate that vertical jump tests may serve as suitable field measurements of anaerobic power for road cyclists, as an alternative to the laboratory-based Wingate anaerobic test.